2010
DOI: 10.1097/wnr.0b013e32833dbd2d
|View full text |Cite
|
Sign up to set email alerts
|

Thyroxine treatments do not correct inner ear defects in tmprss1 mutant mice

Abstract: Complete deficiency of a member of the type II transmembrane serine protease family, tmprss1 (also known as hepsin), is associated with severe to profound hearing loss in mice and a gross enlargement of the tectorial membrane in the cochlea. Levels of thyroxine in these mice have been shown to be significantly lower compared to wild type controls. Since thyroxine is critical for inner ear development, we delivered thyroxine to these mice during the prenatal or postnatal stage of development. Both treatments co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Hepsin deficiency, however, has been linked to aberrant tectorial membrane development and decreased myelination of the auditory nerve. These defects appear to be secondary to either low circulating levels of thyroid hormone or low responsiveness of inner ear tissues to thyroid hormone, but how hepsin would control thyroid hormone action is not evident and as yet unstudied (Guipponi et al 2007, 2008; Hanifa et al 2010). …”
Section: Cellular and Developmental Functions Of Membrane-anchored Sementioning
confidence: 99%
“…Hepsin deficiency, however, has been linked to aberrant tectorial membrane development and decreased myelination of the auditory nerve. These defects appear to be secondary to either low circulating levels of thyroid hormone or low responsiveness of inner ear tissues to thyroid hormone, but how hepsin would control thyroid hormone action is not evident and as yet unstudied (Guipponi et al 2007, 2008; Hanifa et al 2010). …”
Section: Cellular and Developmental Functions Of Membrane-anchored Sementioning
confidence: 99%
“…The significance of the reduced thyroid hormone level in hepsin deficiency‐associated hearing loss was examined. Thyroxine treatment, before and after birth, failed to rescue the hearing loss in hepsin KO mice [100]. Additionally, no differences in serum thyroxine levels were found between WT and Hlb320 mice [79], making it unlikely that the hearing loss caused by hepsin deficiency is secondary to reduced thyroid hormone production.…”
Section: Hepsin Functions In Individual Tissuesmentioning
confidence: 99%
“…Hepsin is also expressed in kidney, pancreas, stomach, prostate and thyroid (Tsuji et al, 1991a,b). Studies of knockout mouse models of hepsin have demonstrated that this protease plays an important role in cochlear development, is involved in regulating levels of the thyroid secreted hormone, thyroxine, and is responsible for pro-HGF activation in the liver (Guipponi et al, 2007; Hanifa et al, 2010; Hsu et al, 2012). …”
Section: Hepsinmentioning
confidence: 99%